Pharmacological Therapy in Sub-Acute Postherpetic Neuralgia Patients: A Case Report - Alamsyah Irwan; Andi Muhammad Takdir Musba (HM Publisher, 2022)
Introduction: Herpes zoster is caused by the reactivation of the varicella-zoster virus. Post-herpetic neuralgia (PHN) is pain due to a zoster that persists 1 month after vesicle development. Usually, the prognosis is good, but some patients continue to suffer from long-term pain. The goal of PHN therapy is to reduce pain and improve quality of life. Antiepileptic drugs and tricyclic antidepressants are the first choices. Case presentation: A 32-year-old man presented with complaints of left-sided headache radiating like electricity to the left eyelid for ± 6 weeks, sudden spikes of nails, numbness/cramping sensation, and pain when touched (allodynia), and hypoesthesia. His previous medical history was herpes zoster, and he received acyclovir and symptomatic therapy such as paracetamol, mefenamic acid, dexamethasone, and cetirizine. The patient presented with a 6-7/10 visual analog scale (VAS) and was diagnosed with subacute post-herpetic neuralgia. The patient received Lyrica (Pregabalin) 50 mg 2 times a day 1 tablet, amitriptyline 10 mg once a day 1 tablet, Ultracet (Tramadol 37.5 mg + paracetamol 375 mg) 3 times a day 1 tablet. After the 14th day, the patient's VAS was reduced to 2/10, but side effects occurred in the form of dry lips and frequent sleepiness, and continued treatment with only Amitriptyline 10 mg/day. Conclusion: Rapid therapy for PHN provides prevention of refractory pain, making it difficult to provide adequate therapy. Giving first-line therapy in subacute PHN using amitriptyline, pregabalin, and tramadol agents have a very good effect in overcoming pain in subacute PHN, but it is necessary to monitor the side effects that occur due to potentiation of these three drugs.